Comparisons of rotavirus VP7-typing monoclonal antibodies by competition binding assay. - Raj, P (1992)
Three sets of neutralizing monoclonal antibodies (MAbs) used to type the outer capsid protein VP7 of four group A rotavirus serotypes (1 through 4) were compared in competition immunoassays. Reciprocal competition was observed for each of the VP7 type 2-, 3-, and 4-specific MAbs. The VP7 type 1 MAbs exhibited variable competition patterns with other VP7 type 1 MAbs. MAb RV4:3, which has been used to recognize antigenic variants within VP7 type 1 strains, showed reciprocal competition with the four VP7 type 3 MAbs (RV3:1, YO-1E2, 4F8, and 159) using a VP7 type 3 virus (SA11) as antigen. MAb 2C9, also prepared against VP7 type 1, reacted with VP7 type 3 strains and competed with a VP7 type 3 MAb, 159, using RRV as antigen. Use of the different sets of VP7 type-specific MAbs in the enzyme-linked immunosorbent assay permitted the recognition of six antigenic variants within VP7 types 1, 2, and 3 among specimens whose VP7 type could not be determined previously with only one set of typing MAbs. These results demonstrate differences of typing ability among these VP7-specific MAbs and emphasize the need to improve the sensitivity of typing systems by incorporating panels of MAbs reacting with several neutralizing epitopes.